On digital intimacy: redefining provider–patient relationships in remote monitoring. (10th October 2019) - Piras, Enrico Maria; Miele, Francesco
Abstract: Remote monitoring has often been thought to lead to a highly structured and standardised care process. Several studies have stressed that patient–provider communication could be hindered if mediated by technologies, leading to an impoverished relationship. We argue that while remote monitoring leads to a redefinition of the patient–provider relationship, it could also offer the opportunity to develop a more intimate acquaintance not possible via only routine visits. The study is part of a clinical trial aimed at assessing the acceptability of a remote monitoring platform for type 1 diabetes. Drawing on practice‐based studies, we focused our analysis on the practice of text message exchange between patients and providers. The 396 conversations were coded with a template analysis, leading to the identification of two main categories: 'knowing the patient' and 'knowing about the patient'. The analysis reveals that the practice of messaging led to the development of a 'digital intimacy', a relationship characterised by a thorough familiarity made possible by electronic devices that extends to face‐to‐face encounters. Drawing on our case, we argue that remote monitoring can foster greater intimacy between patients and providers, which is made possible by the overall increase in the quantity and quality of communication between patients and providers.